Det moralske hospital - sjælesorg og undervisning i Vridsløselille forbedringshus 1859-1868: Danske teologer og blodskam 1680-1770 - Smith, Peter Scharff (Kirkehistoriske Samlinger, 2003)
A Hospital of Morality - Religious instruction and secular education of inmates in Vridsløselille Penitentiary 1859-1868 In 1842 - influenced by the breakthrough of the modern penitentiary in America - a thorough reform of the Danish prison system was decided. Two modern penitentiaries were thus planned and constructed, one based on the so-called Auburn model and the other on the Pennsylvania model. The latter, Vridsløselille, operated as a panoptical facility where constant observation and total isolation was the order of the day. Even the prison church and prison school rooms were constructed panoptical with small wooden-boxes, where in each prisoner was isolated. The point of this regime was to reform offenders individually and religious instruction was to play a major role in this process. It is the subject of this article to show how religious and secular instruction of inmates was carried out under this dramatic regime of total isolation, and it will be discussed how these endeavours influenced the prisoners. The material is supplied by Vridsløselilles archive wherefrom reports (through the years 1859-1868) from for example the appointed priest and teacher are used. Initially the religious aspects of the modem penitentiary and the religious discourse, which these institutions were to operationalize, are presented using both international and Danish sources. The writings of different Danish prison chaplains are for example discussed. Following this a case study of Vridsl0selille penitentiary is presented. Here it is shown how both religion and secular education was assigned a decisive role in the reformation of prisoners, and it is described how authorities went to great lengths to ensure success in this area. Still it is also shown how the end result differed significantly from the intended goal. While the religious instruction undoubtedly had a significant impact on the mental universe of many prisoners several problems also arose. The total isolation drove many insane, and some became obsessed with religious issues. A large number of inmates showed signs of personal disintegration and morale reform did not seem to come about. The teacher at Vridsløselille took pride in teaching many prisoners some very basic skills (reading etc.), but still described his pupils as »gordic knots« that he could not untie. Still the regime of total isolation and religious and secular education of inmates was not abandoned until the 1930’ies.